Perception Matters: Exploring Thai lecturers' views, preferences and needs of MOOCs. Issue 4 (2nd October 2019) - Annamalai, Nagaletchimee; Noonin, Sanit; Buathong, Setthapoom
ABSTRACT: Despite wide recognition of MOOCs, little is known about the lecturers' perception and what are their needs before encouraging them to integrate MOOCs in their pedagogical practices. To gain such an understanding, this study conducted in-depth interviews probing Thai lecturers' perception and paying special attention to their needs in designing their MOOCs. Strengths and challenges in integrating MOOCs were highlighted. The study proposed that for MOOCs to exert power in Thai institutions, it might be necessary for Thai institutions to introduce systematic and effective workshops for lecturers to acquire the skills and confidence to design their MOOCs.